Perceived Coercion Among Patients Admitted in Psychiatric Wards: Italian Results of the EUNOMIA Study - Sampogna, Gaia; Luciano, Mario; Del Vecchio, Valeria; Pocai, Benedetta; Palummo, Carmela; Fico, Giovanna; Giallonardo, Vincenzo; De Rosa, Corrado; Fiorillo, Andrea (Frontiers in Psychiatry, 2019)
The decision to use coercive measures (restraint, seclusion and forced medication) in psychiatric practice is controversial in mental health care. The EUNOMIA study was funded by the European Commission and carried out in 11 countries in order to develop European recommendations for good clinical practice on the use of coercive measures. The aim of the study is to identify sociodemographic and clinical predictors of the levels of perceived coercion in a sample of Italian patients at hospital admission. 294 patients were recruited in five Italian psychiatric hospitals and screened with the MacArthur Perceived Coercion Scale to explore the levels of perceived coercion. Patients were assessed three times: within the first seven days after admission, after 1 and 3 months. At each time point, data on changes of perceived coercion, assessed by the Cantril Ladder of Perceived Coercion Scale, information on coercive measures received during hospitalization and the levels of satisfaction with the received treatments were collected. According to the multivariable regression model, being compulsory admitted (OR: 2.5; 95% CI: 3.3-1.3, p<.0001), being male (OR: 0.7; 95% CI: 0.88-1.4; p<.01), older (OR: .034; 95% CI: .004-.064; p<.05), and less satisfied with received treatments (OR: -.145; 95% CI: -.291 to -.001<.05) are all associated with higher levels of perceived coercion, even after controlling for the use of any coercive measure during hospitalization. Satisfaction with received treatment predicts the levels of perceived coercion and it should represent an important challenge for mental health professionals.